A Implementasi Ekonomi Syari'ah : Marketing Syari'ah: STRATEGI PENETAPAN HARGA DITINJAU PERSPEKTIF EKONOMI SYARI’AH - annuroin, nur muh (IKHTIYAR JURNAL EKONOMI SYARI'AH, 2025)
The background of this study is that the tight competition in the gas industry today, so that companies compete in this very tight competition which aims to create and retain customers. One of their efforts in retaining customers is by setting the best selling price for the product. Because price is a very important part of marketing. In addition, in the distribution process, it must prioritize fairness from distributors in providing prices to stores acording to the HET (highest retail price) of each company, so that companies must really consider setting the selling price of the product by taking into account the products to be sold in order to increase and maintain sales volume. This study is a qualitative field research. The interview targets are those involved in the selling price determination process, such as owners or authorized managers. Data collection uses observation, interview, and documentation methods. While the analysis uses qualitative (non-statistical) analysis which is qualitative descriptive, using inductive thinking. Based on the results of the study, it shows that first: Retail gas sellers use pricing methods and distribution processes that are in accordance with sharia principles and this method is seen in sales data as very effective in increasing sales volume each year. In essence, companies must prioritize the common good and the code of ethics in trading does not have any elements that harm one party.